Antidesma bunius (L.) Spreng. (Foodstuffs and Its Bioactivity) - Marina Silalahi; Endang C. Purba; I. G. A. Rai Sawitri; Riska S. Wahyuningtyas; Novika Sitepu (Journal of Tropical Ethnobiology, 2022)
Antidesma bunius has been long used as food and traditional medicine by vary local communities in Indonesian. This study aims to explain the potential of A. bunius as a food ingredient and its bioactivity. The method used is survey and library research published online at Google Scholar by using keywords such as A. bunius, bioactivities of A. bunius and uses of A. bunius. Antidema bunius is an indigenous plant of Indonesia and has been cultivated in the yard as a shade and source of fruit. The local people in West Java have been used the A. bunius fruits for rujak ingredient which called as rujak buni. As a food ingredient, A. bunius fruit is used as an ingredient for salads and has been processed to be syrup, jelly, sauce and wine. The bioactivity of A. bunius is as an antioxidant, anti-bacterial, anti-cancer, anti-diabetic mellitus, anti-inflammatory and anti-cholesterol. The fruits of A. bunius has potential to be developed as a nutraceutical, especially as an anti-cancer and antioxidant-rich food